Barriers to HIV testing, linkage to care, and treatment adherence: a cross-sectional study from a large urban center of Brazil - MacCarthy, Sarah (2016)
Objective: Early, continued engagement with the HIV treatment continuum can help achieve viral suppression, though few studies have explored how risk factors for delays differ across the continuum. The objective of this study was to identify predictors of delayed diagnosis, delayed linkage to care, and nonadherence to treatment in the city of Salvador, Bahia, Brazil. Methods: Data were collected during 2010 in a cross-sectional study with a sample (n = 1 970) of HIV-infected individuals enrolled in care. Multiple logistic regression analyses identified sociodemographic variables, behaviors, and measures of health service quality that were associated with delayed diagnosis, delayed linkage to care, and treatment nonadherence. Results: For delayed diagnosis, male gender (adjusted odds ratio (AOR), 3.02; 95% confidence interval (CI), 2.0–4.6); age 45 years and older (AOR, 1.67; 95% CI, 1.1–2.5); and provider-initiated testing (AOR, 3.00; 95% CI, 2.1–4.4) increased odds, while drug use (AOR, 0.29; 95% CI, 0.2–0.5) and receiving results in a private space (AOR, 0.37; 95% CI, 0.2–0.8) decreased odds. For delayed linkage to care, unemployment (AOR, 1.42; 95% CI, 1.07–1.9) and difficulty understanding or speaking with a health care worker (AOR, 1.61; 95% CI, 1.2–2.1) increased odds, while posttest counseling (AOR, 0.49; 95% CI, 0.3–0.7) decreased odds. For nonadherence, experiencing verbal or physical discrimination related to HIV (AOR, 1.94; 95% CI, 1.3–3.0) and feeling mistreated or not properly attended to at HIV care (AOR, 1.60; 95% CI, 1.0–2.5) increased odds, while posttest counseling (AOR, 0.34; 95% CI, 0.2–0.6) decreased odds. Conclusions: More attention is needed on how policies, programs, and research can provide tailored support across the treatment continuum.